Assessment Of Health Care Services In Outpatient - Somayeh Shahri; Mohmod Reza Gohari; Seyed Jamaloddin Tabibi; Sara Aghababa (Tehran University of Medical Sciences, 2012)
Background and Aim: The provision of high-quality services is considered as a prerequisite to the success of responsible organizations. Using SERVQUAL model, the present article seeks to delve into the quality of services provided in outpatient clinics as judged by patients in case-study hospitals throughout Tehran. Materials and Methods: This is a cross-sectional descriptive research in which 242 subjects were studied at the outpatient clinics under investigation throughout Tehran using a standardized questionnaire named SERVQUAL (1988). Results: The results of a t-test revealed a meaningful difference between the patients' perception and their expectation about 5 factors (tangible elements, reliability, assurance, accountability and collaboration) affecting the quality of services in clinics. The patients rated ‘assurance' as the most important factor (4.41) and ‘accountability' as the least important of the 5 factors (2.21). Conclusion: The results indicate that the application of SERVQUAL model enables hospital managers to evaluate the quality of services as evaluated by patients as their most important clients and enhance the quality of such services through proper planning and removal of deficiencies.